Incidental Diagnosis of Prostate Cancer by 18F-FDG PET-CT Imaging in a Patient During Post-operative Evaluation for Cecal Cancer - Mutsuddy, Pupree; Kar, Rashmi; Mandal, Tapati; Akhter, Papia; Nath, Khokon Kumar; Siddique, Md Abu Bakker; Begum, Shamim MF (Bangladesh Journal of Nuclear Medicine, 2023)
Incidental high fluorine-18 FDG (fluorodeoxyglucose) uptake in well-differentiated prostate cancer is rare. We reported the case of a 75-year-old man who underwent a whole-body FDG PET-CT (positron emission tomography with computed tomography) scan for post-operative evaluation of caecal cancer and demonstrated no evidence of recurrence. However, a focal hypermetabolic lesion was detected in the right lateral lobe of the prostate. The patient’s prostatic biopsy from the right lobe revealed well-differentiated adenocarcinoma with a Gleason score of six and a raised serum PSA level. Incidental, focally intense FDG uptake in the prostate gland should be considered for further investigations to confirm the presence of prostate cancer. Bangladesh J. Nuclear Med. 26(1): 51-53, 2023